Identification of a Male Sterile Candidate Gene in Lilium x formolongi and Transfer of the Gene to Easter Lily (L. longiflorum) via Hybridization - Moriyama, Takahiro; Shea, Daniel John; Yokoi, Naoto; Imakiire, Seiro; Saito, Takaaki; Ohshima, Hikaru; Saito, Hina; Okamoto, Satoru; Fukai, Eigo; Okazaki, Keiichi (Frontiers in Plant Science, 2022)
Pollen-free varieties are advantageous in promoting cut flower production. In this study, we identified a candidate mutation which is responsible for pollen sterility in a strain of Lilium × formolongi, which was originally identified as a naturally occurred male-sterile plant in a seedling population. The pollen sterility occurred due to the degradation of pollen mother cells (PMCs) before meiotic cell division. Genetic analysis suggested that the male sterile phenotype is attributed to one recessive locus. Transcriptome comparison between anthers of sterile and fertile plants in a segregated population identified a transcript that was expressed only in pollen-fertile plants, which is homologous to TDF1 in Arabidopsis, a gene encoding a transcription factor AtMYB35 that is known as a key regulator of pollen development. Since tdf1 mutant shows male sterility, we assumed that the absence transcript of the TDF1-like gene, named as LflTDF1, is the reason for pollen sterility observed in the mutant. A 30 kbp-long nanopore sequence read containing LflTDF1 was obtained from a pollen fertile accession. PCR analyses using primers designed from the sequence suggested that at least a 30kbp-long region containing LflTDF1 was deleted or replaced by unknown sequence in the pollen sterile mutant. Since the cross between L. × formolongi and Easter lily is compatible, we successfully introgressed the male sterile allele, designated as LflTDF1, to Easter lily. To our knowledge, this is the first report of molecular identification of a pollen sterile candidate gene in lily. The identification and marker development of LflTDF1 gene will assist pollen free lily breeding of Easter lilies and other lilies.